Gambaran Status Gizi pada Pasien Tuberkulosis Anak di Rumah Sakit Umum Cut Meutia - Ariq Murfid; Mauliza Mauliza; Nina Herlina (Pusat riset dan Inovasi Nasional, 2025)
Tuberculosis (TB) is a contagious disease, caused by Mycobacterium tuberculosis, primarily affecting the lungs, but also capable of involving other organs. According to data from the Indonesian Ministry of Health, pediatric TB cases increased by 20.9% in 2021. Similarly, at the Aceh Provincial Health Office reported an 87.3% rise in TB cases in the same year, with North Aceh being one of the regions with the highest prevalence. This study aims to describe the nutritional status of children diagnosed with TB at Cut Meutia Hospital. A descriptive research design was employed, using medical record data of pediatric TB patients. The sampling of technique used was total sampling, comprising 53 children. The findings showed that among the 53 pediatric pulmonary TB cases, most were male (28 children or 52.8%). The most affected age group was school-aged children (29 children or 54.7%). Regarding nutritional status, the majority had good nutrition (32 children or 60.4%). Pulmonary TB was the most prevalent form of TB, found in 41 children (77.4%). When analyzed by age and gender, pulmonary TB was the predominant type across all groups. In conclusion, pulmonary TB was the most common form of TB, predominantly affecting school-aged boys with good nutritional status.